2007
DOI: 10.1111/j.1537-2995.2007.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for red cell phenotypic changes in newly identified, naturally occurring subgroup mutants of the human blood group B glycosyltransferase

Abstract: The genetic background for B(w) phenotypes is very heterogeneous but usually arises through seemingly random missense mutations throughout the last ABO exon. The targeted amino acid residues, however, are well conserved during evolution. Based on analysis of the resulting structural changes in the glycosyltransferase, the mutations are likely to disrupt molecular bonds of importance for enzymatic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Previously, crystallographic and mutational studies of structure-function relationships have been conducted with the catalytic domains of mammalian metal-dependent GT6, bovine α3GT (17, 2225), and human GTA/GTB (18, 2628). In the complexes containing Mn 2+ and UDP or a UDP derivative, the metal interacts with the aspartates of the D X D motif (residues Asp 225 -Val-Asp 227 in α3GT), through a single interaction with Asp 225 and a bidentate interaction with Asp 227 , and also interacts with an oxygen from each of the α- and β-phosphates of the UDP (17, 18).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, crystallographic and mutational studies of structure-function relationships have been conducted with the catalytic domains of mammalian metal-dependent GT6, bovine α3GT (17, 2225), and human GTA/GTB (18, 2628). In the complexes containing Mn 2+ and UDP or a UDP derivative, the metal interacts with the aspartates of the D X D motif (residues Asp 225 -Val-Asp 227 in α3GT), through a single interaction with Asp 225 and a bidentate interaction with Asp 227 , and also interacts with an oxygen from each of the α- and β-phosphates of the UDP (17, 18).…”
Section: Resultsmentioning
confidence: 99%
“…Sera of B v individuals contain a form of anti -B; no GTB activity could be detected. Of 18 Hong Kong Chinese with B v red cells, 17 had a B allele containing 695T > C, Leu232Pro ( Bw11 [346] ) and one had a B allele containing 721C > T, Arg241Trp ( Bw03 [261] ); no mutation was detected in the coding region of the B gene of an AB v individual [351] . Of 18 Hong Kong Chinese with B v red cells, 17 had a B allele containing 695T > C, Leu232Pro ( Bw11 [346] ) and one had a B allele containing 721C > T, Arg241Trp ( Bw03 [261] ); no mutation was detected in the coding region of the B gene of an AB v individual [351] .…”
Section: B Mmentioning
confidence: 99%
“…Numerous other ABO alleles responsible for variant B phenotypes have been described, mostly as B w [159,215,261,317,346] . A structural analysis, based on the crystal structure of GTB, demonstrated that the mutations in variant B alleles are likely to disrupt molecular bonds important for enzyme function [346] .…”
Section: Other Subgroups Of Bmentioning
confidence: 99%
“…Single‐nucleotide alteration in the ABO gene can affect the enzyme activity or protein quantity 1‐7. Several different techniques have been used to elucidate the mutation–function relationship of a mutant ABO glycosyltransferase (GT).…”
mentioning
confidence: 99%
“…Several different techniques have been used to elucidate the mutation–function relationship of a mutant ABO glycosyltransferase (GT). The crystal X‐ray diffraction and three‐dimensional (3D) molecular modeling have described the conformation of the mutant enzyme 1‐4. Some in vitro expression studies have evaluated the expression level of ABO antigen on cell lines transfected with plasmids containing recombinant mutants, and flow cytometry analysis of red blood cells (RBCs) has been utilized to characterize different ABO subgroups .…”
mentioning
confidence: 99%